Geomorphology, soils and palaeosols of the Chencha area (Gamo Gofa, south western Ethiopian Highlands). (March 2019) - Coltorti, Mauro; Pieruccini, Pierluigi; Arthur, Kathrin J.W.; Arthur, John; Curtis, Matthew
Abstract: The landscape of the Chencha Highland (south western Ethiopia) is characterized by flat plateau bordered by steep slopes affected by landslides and dissected by concave valleys and gullies. Coalescing alluvial fans are found along the eastern piedmont at the transition to the Lake Abaya shores. A major rift-plateau escarpment, with minor synthetic and antithetic faults, is located along the eastern slopes of the highlands. Soil erosion is a widespread process and the soil cover is usually thin and discontinuous. Immature Cambisols formed on colluvial deposits containing lithic tools, pottery fragments and charcoal represent the most recent phase of soil formation. They are related to the clearance of the original forest cover and the introduction of extensive agricultural and pastoral practices. On the slopes these soils locally unconformably overlie reddish, strongly weathered buried Nitisols and Luvisols that can be classified as Palaeoedlisols with formation of saprolite. Thicker and better preserved Palaeoeldisols can be found on the summit plateau, due to reduced runoff erosion. Different generations of clay illuviation indicate that they underwent polycyclic processes, recording soil processes probably older than Holocene. Along the slopes, gully erosion exhumed a palaeo-gully system infilled by colluviums of soils and buried soils containing Middle Stone Age artifacts suggesting that important slope degradational processes occurred also during the Late Pleistocene. Buried brownish soils in these infillings show moderate clay illuviation that indicates short-lived climatic amelioration and phases of slope stability. Graphical abstract: Image 1 Highlights: Late Holocene soil cover is strictly related to land use and human impact. Plateau's summit surfaces preserve palaeosols formed under older soil formation conditions and greater geomorphic stability. Clay illuviation is still the main ongoing soil process also on younger colluvial soils.